Cyber Threat Map of the Central Sahel Region : A Fragile Fundation of Development - Szulcsányi, Viktor; Vörös, Gyula (Journal of Central and Eastern European African Studies, 2025)
The developing, but often fragile digital infrastructure of the Central Sahel region – especially the countries of Burkina Faso, Mali, Niger and Chad – are recent targets of various cyberattacks. Despite the financial situation of these countries, cybercriminals and even state-sponsored threat actors are continuously exploiting public internet-facing IT systems that are affected by security vulnerabilities. This study aims to describe the current state of the region’s digital infrastructure and cyber threat landscape, while identifying the key aspects of sustainable growth and the potential limitations of the countries’ cybersecurity posture. Although the region had limited access to the internet in the past, it has witnessed significant increase in the number or households with mobile internet connectivity. This digital expansion affects the daily life of the population, alongside the difficulties of infrastructional underdevelopment, social and financial inequalities and the political instability and all of these factors are leading to a fragile digital environment. Social media usage had also shown a significant increase in the last decade in this region, and it also gave room for political influence, spreading propaganda or deepfake messages and even for the online requitment of armed groups (e.g. JNIM, ISGS). This paper also provides an overview of the current regulations and legal landscape of the countries in this region. In this constantly evolving territory, the legal and institutional background of cybersecurity governance is of key importance in addressing cyber threats and incidents. This study also discusses the main cyber events affecting the Central Sahel region in the recent years and aims to analyse the presence, operational capacity and maturity level of national CERTs and international partnerships to address cyber threats.